2007
DOI: 10.1245/s10434-007-9667-2
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab Shows Activity in Colorectal Cancer Patients With Tumors for Which FISH Analysis Does Not Detect an Increase in EGFR Gene Copy Number

Abstract: EGFR FISH analysis does not seem to be a sufficiently robust test for selecting candidate CRC patients for cetuximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 29 publications
3
54
0
1
Order By: Relevance
“…More recently, increased EGFR gene copy number as detected by fluorescence in situ hybridization (FISH) was associated with response to cetuximab or panitumumab [33]. This has been contradicted by findings that FISH analysis of EGFR amplification does not select all colorectal cancer patients who may benefit from cetuximab therapy [34]. These discrepancies could be explained by tumor heterogeneity, presence of heterogeneous EGFR populations with different levels of low-and high-affinity sites, lack of standardized EGFR testing methods, and poor correlation between EGFR protein and DNA levels [17,35].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
“…More recently, increased EGFR gene copy number as detected by fluorescence in situ hybridization (FISH) was associated with response to cetuximab or panitumumab [33]. This has been contradicted by findings that FISH analysis of EGFR amplification does not select all colorectal cancer patients who may benefit from cetuximab therapy [34]. These discrepancies could be explained by tumor heterogeneity, presence of heterogeneous EGFR populations with different levels of low-and high-affinity sites, lack of standardized EGFR testing methods, and poor correlation between EGFR protein and DNA levels [17,35].…”
Section: Egfr and Colorectal Cancermentioning
confidence: 99%
“…However, tumour response was observed in colorectal tumours without an increase of EGFR copy number (Italiano et al, 2008) and discrepant results were observed when EGFR copy number was assessed by quantitative PCR and not by FISH (Vallbohmer et al, 2005;Lenz et al, 2006;Khambata-Ford et al, 2007).…”
Section: Pik3ca Mutations and Loss Of Pten Expressionmentioning
confidence: 96%
“…Indeed, BRAF V600E mutation seems to be a marker of poor prognosis (9,10,14,15). Furthermore, studies that examined PIK3CA mutations, loss of PTEN expression, EGFR gene copy number, and polymorphisms of fragment c g receptors have reported conflicting results (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)). Finally, mRNA expression level of amphiregulin and epiregulin seems to be of limited clinical interest because of the inability to set an appropriate threshold limit (28,29).…”
Section: Introductionmentioning
confidence: 99%